The efficacy and safety of Chinese herbal medicine Shugan Sanjie decoction in the treatment of uterine fibroids: a systematic review and meta-analysis - Zhang, Yang; Wei, Junfan; Gao, Chanchan; Feng, Shenyang; Wang, Haiying; Chai, Junjie; Zhu, Yini; Yuan, Yuan; Ren, Lirong (Frontiers in Pharmacology, 2025)
BackgroundShugan Sanjie Decoction (SGSJ) is a commonly used Chinese medicine prescription for the treatment of uterine fibroids (UFs). However, there is still a lack of evidence for its effects and safety. To systematically assess the efficacy and safety of SGSJ in conjunction with Mifepristone [MFP] or Leuprolide acetate [LA] for the treatment of UFs, thereby providing a reference for clinical medication.ObjectiveTo systematically assess the efficacy and safety of SGSJ in combination with MFP or LA for the treatment of UFs, thereby providing a basis for clinical medication decisions.MethodsEight digital medical databases were systematically searched to identify randomized controlled trials (RCTs) evaluating the use of SGSJ combined with MFP or LA for the treatment of UFs. The search spanned from the inception of each database to July 2024. Risk of Bias (ROB) 2.0 and RevMan 5.3 software were utilized for systematic review and meta-analysis. Eligible studies comprised RCTs comparing SGSJ plus MFP or LA with MFP or LA alone. The primary outcome was the Clinical Effective Rate (CER). Secondary outcomes included (1) Uterine Fibroid Volume (UFV) (2), Uterine Volume (UV) (3), Serum Sex Hormone Levels [Follicle-Stimulating Hormone (FSH), Luteinizing Hormone (LH), Estradiol (E2), Progesterone (P)], and (4) Traditional Chinese Medicine Syndrome Scores (TSS).ResultsThe meta-analysis comprised 12 RCTs with 952 participants. The results of meta-analysis showed that the total effective rate of SGSJ or combined with MFP or LA in the treatment of UFs [RR = 1.26, 95% CI (1.19, 1.34), P < 0.00001], which was statistically significant compared with the MFP or LA group and superior to the MFP or LA group (P < 0.05).ConclusionAt present, there are evidence shows that SGSJ combined with MFP or LA improves CER, reduces UFV, and modulates sex hormone levels. However, due to the poor methodological quality and high heterogeneity of the included trials, our conclusions should be interpreted with caution. Future studies should prioritize rigorous RCTs with standardized treatment protocols, extended follow-up, and comprehensive safety assessments to identify SGSJ as a reliable treatment option for UFs.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024506017